Multisite Study of Women Living With HIV's Perceived Barriers to, and Interest in, Long-Acting Injectable Antiretroviral Therapy. (1st July 2020) - Philbin, Morgan M.; Parish, Carrigan L.; Kinnard, Elizabeth N.; Reed, Sarah E.; Kerrigan, Deanna; Alcaide, Maria L.; Cohen, Mardge H.; Sosanya, Oluwakemi; Sheth, Anandi N.; Adimora, Adaora A.; Cocohoba, Jennifer; Goparaju, Lakshmi; et al.
Abstract : Background: Adherence to antiretroviral therapy (ART) is imperative for viral suppression and reducing HIV transmission, but many people living with HIV report difficultly sustaining long-term adherence. Long-acting injectable (LAI) ART has the potential to transform HIV treatment and prevention. However, little LAI ART–related behavioral research has occurred among women, particularly outside of clinical trials. Setting: Six Women's Interagency HIV Study sites: New York, Chicago, Washington DC, Atlanta, Chapel Hill, and San Francisco. Methods: We conducted 59 in-depth interviews with women living with HIV across 6 Women's Interagency HIV Study sites (10 per site; 9 at Washington DC). We interviewed women who were not included in LAI ART clinical trials but who receive care at university settings that will administer LAI ART once it is approved. Interviews were recorded, transcribed, and analyzed using thematic content analysis. Results: Most women enthusiastically endorsed monthly LAI ART and would prefer it over pills. The following 3 reasons emerged for this preference: (1) convenience and confidentiality, (2) avoiding daily reminders about living with HIV, and (3) believing that shots are more effective than pills. Challenges remain, however, specifically around (1) medical mistrust, (2) concerns about safety and effectiveness, (3) pill burden for HIV and other conditions, and (4) barriers to additional medical visits. Conclusions: Most women preferred LAI ART over daily pills given its benefits, including convenience, privacy, and perceived effectiveness. Future research should incorporate more women into LAI ART trials to better understand and align development with user concerns and preferences to enhance uptake. Abstract : Supplemental Digital Content is Available in the Text.